The political economy of foreign investment and industrial development: the Philippines, Malaysia and Thailand in comparative perspective - Montes, Manuel F (Archīum Ateneo, 2019)
This article examines the contribution of foreign investment to industrial development by comparing the Philippine experience with two ASEAN neighbors: Malaysia and Thailand. Instead of viewing a failure to attract foreign investment as a binding development constraint, we focus on the appropriateness of such flows for industrial upgrading. Likewise, we underscore political economy factors—particularly the presence of effective state interventions and conducive state-business ties—as prime features of countries that have leveraged FDI for more successful industrial development. Without discounting flaws in these interventions in the cases of Thailand and Malaysia, we find that such forms of government involvement have been vital in driving both countries’ strong investment and industrial growth records relative to that of the Philippines. Revived industrial policy initiatives in developing Asia would be well-advised to heed these lessons on investment-related intervention, so as to reorient their investment policies for maximum impact on industrial development in the years ahead.